Detection of blood thrombin enzyme in surimi-based products by using polymerase chain reaction (PCR) method - Alina A.R.; Nur Nadiah Syuhada A.S.; Sharifah N.R.S.A.; Siti Mashitoh A.; Nurul Aqilah A.S.; Nurul Mawaddah A.H.; Nurulhuda M.S.; Ummi Syuhada H.S.; Syamsul K.M.W.; Nurul Farah Sakinah A. (2024)
Indexed by Scopus